Impact of yellow head virus outbreaks in the whiteleg shrimp, Penaeus vannamei (boone), in Thailand - S. Senapin (2018)
Yellow head virus (YHV) is known as a major pathogen in the black tiger shrimp, Penaeus (Penaeus) monodon. It can also cause serious mortality in farmed whiteleg shrimp, Penaeus (Litopenaeus) vannamei. However, there is no published information on the economic and/or production impact of the disease in P. vannamei. Shrimp with gross signs of YHV disease (faded body colour and 60-70% mortality) were observed in 20 study farms rearing P. vannamei in the central part of Thailand from the end of 2007 through early 2008. The estimated economic loss for these farms according to the Thai Animal Aquaculture Association was approximately US$3 million. Detailed sequence analysis of RT-PCR amplicons from shrimp in all the study ponds revealed the presence of YHV Type 1b (YHV-1b) alone (characterized by a 162-bp deletion in the ORF3 region encoding the structural gene for gp116) and the absence of YHV Type 1a (YHV-1a), the original YHV type reported from Thailand. Despite the large 162-bp deletion (= 54 deduced amino acids) in the gp116 structural gene, histopathology of YHV-1b infections was identical to that of YHV-1a infections, and electron microscopy revealed that YHV-1b virions were morphologically indistinguishable from those previously reported for YHV-1a. In addition, an existing commercial RT-PCR detection kit and an immunochromatographic test strip for the detection of YHV were proven to have been valid tests for both YHV-1b and YHV-1a. The source of the virus for these outbreaks was unlikely to have been the post-larvae used to stock the ponds, as they were derived from domesticated specific pathogen-free stocks free of YHV. Thus, it is possible that they originated from an unknown, natural reservoir. © 2010 Blackwell Publishing Ltd.